A highly sensitive wireless nitrogen dioxide gas sensor based on an organic conductive nanocomposite paste. Issue 14 (20th March 2019) - Kim, Sung Gun; Jun, Jaemoon; Lee, Jun Seop; Jang, Jyongsik
Abstract : The conducting nanocomposite paste composed of multidimensional hollow nanoparticles and PANI:PSS easily forms sensing area in the wireless sensor tag. Abstract : Hazardous gas sensor technology in a wireless system is needed urgently for diverse applications ranging from the workplace to the battlefield. However, there are several limitations of the wireless gas sensing system such as high cost and poor sensitivity and selectivity for applications in real life. Here, a radio frequency identification (RFID)-based wireless sensor system is fabricated using an organic conductive nanocomposite paste composed of multidimensional Fe2 O3 hollow nanoparticles (M_FeHNPs) and polystyrene sulfonic acid-doped polyaniline (PANI:PSS). The conductive paste acts as an RFID tag antenna pattern and sensing transducer in the RFID sensor tag. This RFID-based wireless sensor shows ultrahigh sensitivity (up to 0.5 ppm) to NO2 with very low processing cost. In addition, the organic conducting paste based RFID sensor system displays a long-distance operating range and high flexibility, which may offer practical use in a wearable device for wireless sensing.